2014
DOI: 10.3748/wjg.v20.i32.11422
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tandospirone in patients with irritable bowel syndrome-diarrhea and anxiety

Abstract: Tandospirone is effective and can be combined with pinaverium in IBS-D patients with anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…231,232 When the same agent was used in patients with IBS and anxiety, the fraction of patients responding with at least 50% decrease in pain was significantly higher than that in the placebo group. 233 A recent meta-analysis of controlled trials in depression showed a relatively high incidence of adverse effects on gastrointestinal function, which could contribute to these discrepancies. 234 …”
Section: Buspirone In Ibdmentioning
confidence: 98%
“…231,232 When the same agent was used in patients with IBS and anxiety, the fraction of patients responding with at least 50% decrease in pain was significantly higher than that in the placebo group. 233 A recent meta-analysis of controlled trials in depression showed a relatively high incidence of adverse effects on gastrointestinal function, which could contribute to these discrepancies. 234 …”
Section: Buspirone In Ibdmentioning
confidence: 98%
“…Tandospirone is available only in China and Japan. Positive effects on abdominal pain ratings (≥ 50% reduction compared with baseline) among IBS patients were reported in a study confounded by simultaneous use of pinaverium [ 51 ], but it was not better than placebo in a study involving patients with functional dyspepsia [ 52 ]. With these data at hand, the clinical recommendation for buspirone is to use it when early satiety, fullness, and nausea dominate a DGBI.…”
Section: Central Neuromodulatorsmentioning
confidence: 99%
“…The effect of central 5-hydroxytryptamine (5-HT) and its receptor, 5-HT1A receptor (HTR1A), on perception and processing of pain have become increasingly recognized over time. For example, HTR1A has been associated with chronic stress-induced visceral hypersensitivity and neuropathic pain in pre-clinical rodent studies, and many clinical trials have suggested that activation of HTR1A (either directly or via 5-HT reuptake inhibition) in the CNS might ameliorate psychiatric and gastrointestinal symptoms of IBS [15,16]. Recently, down-regulation of HTR1A in some nuclei of the limbic system (including the ACC and IC) was observed in rats with viseral hypersensitivity induced by chronic water avoidance stress (WAS), and local up-regulation of HTR1A using lentiviral constructs or direct activation with a selective agonist could reverse the visceral hypersensitivity and anxiety-like behaviours [17,18].…”
Section: Introductionmentioning
confidence: 99%